Diplomasi Publik Butet Manurung dalam Rangka Penguatan Ketahanan Masyarakat Adat (Studi pada Masyarakat Adat di Jambi) - Kartikasari, Wahyuni (Jurnal Ketahanan Nasional, 2024)
Based on research on the role of Butet Manurung with Sokola Rimba, this article examines her activities in developing the potential of indigenous communities with Sokola Rimba aims to reveal efforts to strengthen the potential of indigenous communities in Indonesia in order to increase the resilience of indigenous communities and culture, thereby relating to the issue of Indonesian national resilience. A further aim is to see this connection with the study of public diplomacy where the international awards received from his activities with Sokola Rimba made Butet Manurung play the role of being an Indonesian public diplomacy actor in the international arena. The research was conducted using qualitative methods and secondary data from news references and qualitative research on Butet Manurung and theoretical explanations, concepts and case studies about social, cultural and community resilience, public diplomacy and cultural diplomacy. Because indigenous communities play a crucial role in preserving ecosystem balance and enhancing resilience of both life and communities, research on Butet Manurung and Sokola Rimba demonstrates the need of studying indigenous communities resilience. The collective rights of indigenous peoples, including the right to use natural resources, enable them to determine their own lives, self-regulate, be independent and no longer marginalized. They have the right to participate in determining planning, development and sustainable use of their customary territories in accordance with local wisdom. Furthermore, Butet Manurung's existence in the international arena makes him an actor in Indonesian public diplomacy in carrying important messages such as survival and human rights, environmental and ecosystem maintenance and life values and will ultimately strengthen the study of P to P diplomacy as an alternative from G to G diplomacy.